The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4018/jismd.2013040101
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Improving Business Process Performance through Positive Deviance

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The focus on negative deviations is in line with the observation that inductive BPM approaches, including process mining, often put a strong focus on "responding to pain points" [20], while the exploration of opportunities is less emphasized. However, research has shown that processes can be improved by learning from positive deviations [23] or experience gained through past executions [9]. We find the tendency to look at negative deviations at the start of the analysis somewhat surprising.…”
Section: Discussion and Limitationsmentioning
confidence: 62%
“…The focus on negative deviations is in line with the observation that inductive BPM approaches, including process mining, often put a strong focus on "responding to pain points" [20], while the exploration of opportunities is less emphasized. However, research has shown that processes can be improved by learning from positive deviations [23] or experience gained through past executions [9]. We find the tendency to look at negative deviations at the start of the analysis somewhat surprising.…”
Section: Discussion and Limitationsmentioning
confidence: 62%
“…These approaches are problem-based, in the sense that they aim at improving issues or bottlenecks (Van den Bergh et al , 2014; Grisold et al , 2019) and thus mainly investigate the problem space of processes. As an example, lean management classifies different types of waste to be avoided, while non-value-adding process activities should be eliminated. Imitation-based approaches like benchmarking (König et al , 2019) and positive deviance (Setiawan and Sadiq, 2013) search for superior process designs with the aim to imitate (part of) the process' design, which causes this effective behavior. Pattern-based approaches build on this imitation rationale by abstracting from various real-world examples to sketch out useful and proven solutions. Representatives of this group are best practices of process redesign (Reijers and Liman Mansar, 2005), explorative process design patterns (Rosemann, 2020), customer-centric design patterns (Frank et al , 2020) and the Rethink of Process (RePro) principles (Vanwersch et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Imitation-based approaches like benchmarking (König et al , 2019) and positive deviance (Setiawan and Sadiq, 2013) search for superior process designs with the aim to imitate (part of) the process' design, which causes this effective behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Information systems are the arrangement of people, data, processes, and information (IT) or information technology that interact to collect, process, store, and provide as the output of information needed to support an agency or organization [1]. Meanwhile, according to Laudon and Laudon information systems are interrelated components that work together to collect, process, store, and display information to support decision making, coordination, regulation, analysis, and visualization in an organization [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%